Discussing HPV and oropharyngeal cancer in dental settings: gender and provider-type matter. Issue 12 (2nd December 2021) - Daley, Ellen M.; Thompson, Erika L.; Beckstead, Jason; Driscoll, Annelise; Vamos, Cheryl; Piepenbrink, Rumour P.; Desch, Jill; Merrell, Laura; Richardson Cayama, Morgan B.; Owens, Heather; Lovett, Sharonda M.
ABSTRACT: Human papillomavirus (HPV) is the most common sexually transmitted infection in the US and the leading cause of oropharyngeal cancer (OPC), an oral cancer most often identified by dental providers. Given the rise in HPV-associated OPC and recent Food and Drug Administration (FDA) approval of the HPV vaccine to prevent OPC, dental providers have a unique role in HPV prevention. This study assessed US adults' comfort levels discussing HPV and OPC with dental providers. An online survey platform was used to recruit a nationally representative sample of US adults (n = 300). The questionnaire assessed participants' knowledge, acceptability, and comfort discussing HPV-related topics with dental providers. SPSS 24 was utilized for data analyses. In general, participants reported feeling comfortable discussing HPV and OPC with dental providers. Participants reported feeling more comfortable with dentists than dental hygienists when discussing ( t =  2.85, p < .01) and receiving recommendations about the HPV vaccine ( t = 2.09, p < .05). Participants were less comfortable discussing HPV as a risk factor for OPC compared to non-HPV related risk factors ( t = 2.94, p < .01). Female participants preferred female providers, whereas male participants had no preference. Previous research has indicated dental providers recognize their role in HPV prevention, but research is needed to understand patients' perceptions of dental providers' role in HPV prevention. Findings demonstrate that US adults are comfortable discussing HPV and OPC with dental providers, which may be key to OPC-HPV prevention. Future research is needed to facilitate HPV communication between patients and dental providers.